Parentage Analysis in a Green Sea Turtle (Chelonia mydas) Population From French Polynesia Reveals a Tendency for Inbreeding and Unexpected Plasticity in Reproductive Behaviour - Violaine Dolfo; Cécile Gaspar; Miri Tatarata; Emilie Boissin; Serge Planes (Ecology and Evolution, 2025)
ABSTRACT The reproductive systems of natural populations can significantly impact their genetic diversity by either preventing or promoting inbreeding. Therefore, it is crucial to have a comprehensive understanding of the mating system to evaluate a population's ability to maintain genetic diversity over time. In this study, we examine the mating system of an endangered population of green sea turtles in Tetiaroa, French Polynesia. We determine if different mating behaviours serve as strategies to avoid inbreeding. We genotyped 107 nesting females and 1483 hatchlings from 549 nests and used 23 microsatellite markers to reconstruct the genotypes of the sires. We assessed the level of inbreeding and relatedness among the parent pairs and explored the correlation between relatedness and indicators of reproductive success. We investigated the mating behaviours of both males and females and determined whether specific behaviours were linked to different levels of relatedness. We explored for the first time the relatedness bias of mating behaviours in green turtles. Our results showed that the global Fis was significant in the population, and the levels of relatedness were higher than expected through random mating, indicating inbreeding and non‐random partner selection for related mates. No mating behaviours were associated with lower relatedness levels, suggesting inbreeding tolerance or preference in this population. Finally, we discovered unexpected plasticity in the reproductive frequency of females, the length of the inter‐nesting interval, and the relative timing of breeding and nesting. If confirmed in other populations and with a larger sample size, these new findings may reshape our understanding of the green turtle's intricate reproductive system.